Dynamics of Epstein‐Barr viral load after hematopoietic stem cell transplantation and effect of preemptive rituximab therapy. Issue 6 (24th November 2016) - Raberahona, Mihaja; Wackenheim, Chloe; Germi, Raphaele; Carré, Martin; Bulabois, Claude‐Eric; Thiébaut, Anne; Lupo, Julien; Semenova, Touyana; Cahn, Jean‐Yves; Morand, Patrice; Epaulard, Olivier
Abstract: Background: Epstein‐Barr virus (EBV) displays oncogenic properties, particularly in the immunocompromised host. Notably, hematopoietic stem cell transplantation (HSCT) recipients with a detectable blood EBV viral load (BEBVL) are considered at higher risk of post‐transplant lymphoproliferative diseases (PTLD). Therefore, BEBVL is monitored after HSCT, and preemptive rituximab may be used in patients with high values. However, little is known about post‐HSCT BEBVL dynamics, and the threshold that should lead to anti‐CD20 therapy is poorly defined. Methods: We retrospectively analyzed the post‐HSCT BEBVL of 332 adult HSCT recipients in our center from 2005 to 2013, including the effect of rituximab. Results: Detection of BEBVL >100, 1000, 5000, 10 000, and 50 000 copies/mL occurred in, respectively, 77.7%, 69.6%, 37.0%, 27.1%, and 7.5% of the patients after a respective median time of 9, 14, 15, 16, and 14 weeks. No BEBVL threshold was associated with an overall survival difference. Seventy‐eight patients received rituximab, with a BEBVL decrease in most. Among patients with detectable BEBVL, long‐term survival did not differ in rituximab treated and non‐treated, except for patients with BEBVL ≥50 000. Only one case of PTLD was observed. Conclusions: BEBVL is frequently detectable after HSCT, but suggests no strong association with survival. Preemptive rituximab therapy threshold remains to be defined.